2011
DOI: 10.1016/j.aquaculture.2011.01.029
|View full text |Cite
|
Sign up to set email alerts
|

A baseline method for benchmarking mortality losses in Atlantic salmon (Salmo salar) production

Abstract: On-farm databases provide a large diversity of information regarding fish health and stock performance. Mortality records held in on-farm database are indicators of fish health status and of great interest for studying fish health, such as patterns of diseases. Mortality records from a Scottish Atlantic salmon production database of one company were used to develop a method of benchmarking production losses due to mortality. The records used concerned mortality loss numbers of Atlantic salmon in the seawater p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
73
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 15 publications
3
73
0
1
Order By: Relevance
“…The majority of mortality, both in numbers and biomass, is from unspecified causes throughout the course of the whole 148 production cycle. The results agree broadly with those reported by Soares et al (2011), who studied salmon mortality across over eighty farms in Scotland from one company, although that study found far more mortality attributable to disease. According to staff from the company that supplied the data, a certain amount of fish can be expected to die from no apparent attributable cause and this is common for all farmed salmon production.…”
Section: Mortality In Scottish Atlantic Salmon Productionsupporting
confidence: 82%
See 1 more Smart Citation
“…The majority of mortality, both in numbers and biomass, is from unspecified causes throughout the course of the whole 148 production cycle. The results agree broadly with those reported by Soares et al (2011), who studied salmon mortality across over eighty farms in Scotland from one company, although that study found far more mortality attributable to disease. According to staff from the company that supplied the data, a certain amount of fish can be expected to die from no apparent attributable cause and this is common for all farmed salmon production.…”
Section: Mortality In Scottish Atlantic Salmon Productionsupporting
confidence: 82%
“…This may be attributable to several causes, as diseases were not specified, but of most concern over the last decade, has been mortality and damage due to sea-lice. Despite development of in-feed treatments such as emamectin 150 benzoate and preventative measures such as fallowing and single year classes, sea-lice can still cause major losses in Scottish salmon farms (Soares et al 2011). Notifiable diseases such as IPN or ISA have been of little concern since the widespread uptake of vaccination programmes against these diseases.…”
Section: Mortality In Scottish Atlantic Salmon Productionmentioning
confidence: 99%
“…Such analyses have been performed to understand patterns of mortality and their causes in pigs (Chagnon et al 1991, Shankar et al 2009) and poultry (Carver et al 2000, Tabler et al 2004. A preliminary investigation into patterns of mortality in salmon was performed by Soares et al (2011), who found fluctuations in mortality rates and constructed a demonstrative benchmark for salmon mortality in Scotland.In this study, we built on this analysis to examine the causes of mortality and explanatory factors for variations in mortality, to determine whether this mortality benchmark can be generalised, or whether it is dominated by site-specific and unpredictable effects. We investigated which risk factors (such as temperature, age, or site) were associated with variation in mortality during the marine phase of Atlantic salmon production.…”
mentioning
confidence: 99%
“…These databases have an important role to play in the investigation and understanding of diseases, since they store valuable data for epidemiologists and can allow quantification of production losses over time. Furthermore these data can facilitate development of effective disease control strategies (Menzies et al 1996, Crockford et al 1999) through epidemiology.One of the most important variables recorded at the farm level is fish mortality rate (MacIntyre 2008, Anonymous 2009, Soares et al 2011, which may include the cause of death, e.g. environmental problems, predators or disease (MacIntyre 2008, North et al 2008.…”
mentioning
confidence: 99%
See 1 more Smart Citation